2014
DOI: 10.1021/am508157m
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of Zwitter-Wettable Nanostructured Films

Abstract: Manipulating surface properties using chemistry and roughness has led to the development of advanced multifunctional surfaces. Here, in a nanostructured polymer film consisting of a hydrophilic reservoir of chitosan/carboxymethyl cellulose capped with various hydrophobic layers, we demonstrate the role of a third design factor, water permeation rate. We use this additional design criterion to produce antifogging coatings that readily absorb water vapor while simultaneously exhibiting hydrophobic character to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 24 publications
5
69
0
2
Order By: Relevance
“…[1][2][3][4] Over the last few decades, an extensive research studies have been reported to prevent the formation of fog and frost on solid surfaces by different approaches including superhydrophobic coatings, 5-7 superhydrophilic coatings 8,9 and combinations of both hydrophilic and hydrophobic properties in the coating. [10][11][12][13][14][15] Hydrophilic surfaces that have a water contact angle of less than 5 o exhibit excellent anti-fog properties because they allow water droplets to spread uniformly to form a thin water film, which reduces light scattering. 9,16,17 In general, superhydrophilicity can be obtained by various chemical and physical methods.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Over the last few decades, an extensive research studies have been reported to prevent the formation of fog and frost on solid surfaces by different approaches including superhydrophobic coatings, 5-7 superhydrophilic coatings 8,9 and combinations of both hydrophilic and hydrophobic properties in the coating. [10][11][12][13][14][15] Hydrophilic surfaces that have a water contact angle of less than 5 o exhibit excellent anti-fog properties because they allow water droplets to spread uniformly to form a thin water film, which reduces light scattering. 9,16,17 In general, superhydrophilicity can be obtained by various chemical and physical methods.…”
Section: Introductionmentioning
confidence: 99%
“…One approach, the so‐called the hydrophilicity‐induced antifogging or the wet‐style antifogging, relies on modification of a substrate with hydrophilic materials, which can avoid fogging by strongly interacting with water molecules. [ 4,5 ] When this high affinity for water is synergistically combined with nanotexture, a superhydrophilic surface is generated; this surface exhibits extremely low water contact angle (<5°) and induces film‐wise condensation via capillary condensation upon temperature difference, maintaining excellent optical properties under fogging conditions. [ 6 ] However, when the amount of water condensed exceeds the capacity of the film, the flooded water layer on top causes substantial image distortion.…”
Section: Figurementioning
confidence: 99%
“…Alternatively, zwitter‐wettable films that simultaneously exhibit hydrophobicity and hygroscopic properties have been proposed. [ 5 ] These heterostructured films comprise a hydrophilic reservoir and a nanoscale thin hydrophobic capping layer in which the water vapor can readily permeate through and interact with the underlying hydrophilic reservoir. While the zwitter‐wettability allows water vapor to preferably condense into the hydrophilic reservoir instead of the surface to exhibit antifogging property, the combination of surface hydrophobicity and high water vapor permeability is inevitably accompanied by high water contact angle hysteresis.…”
Section: Figurementioning
confidence: 99%
“…Therefore, the catechol is important for strong wet adhesion. Many interesting methods based on catechol have been developed to modify almost all types of surfaces, and it is a universal method . Most of the reported works are coated with DA only, followed by another reaction, such as alkali treatment .…”
Section: Introductionmentioning
confidence: 99%
“…The water can potentially weaken the interactions between polymers and surfaces. Fortunately, catechol‐functionalized polymers can enhance the surface adhesion and enable a mechanically robust coating tightly on the surface of the intrinsic hydrophobic polymers . This is of particular interest for practical applications.…”
Section: Introductionmentioning
confidence: 99%